DIMENSIONAL ACCURACY OF ALGINATE IMPRESSION MATERIAL USING KORSOLEX DISINFECTANT THROUGH CAD CAM - Krisna Malay, Kausalyah; Sivaswamy, Vinay; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Alginate is an elastic, irreversible hydrocolloid impression material. It is most frequently used in dental practice. Disinfecting the impression material is a vital step to prevent cross-contamination. The aim of this research is to evaluate the effect of Korsolex, an alkaline glutaraldehyde-based disinfectant, on the dimensional stability of commonly used impression material, alginate. Objective: To determine an economical yet effective method of disinfecting impressions that can be used routinely in clinical practice. Methodology: The study was conducted with 45 samples of alginate impression made on a Type III gypsum model. The samples were equally divided into three groups of 15 each (control, post-immersion (10 min), and post-immersion (20 min). Impressions in the control group were washed with tap water. The two test groups were immersed in Korsolex disinfectant solution for 10 minutes and 20 minutes, respectively. Casts were made from all the impressions, and predetermined points were measured on the casts. The casts were scanned using an optical scanner of a CAD/CAM milling machine. The distance between premolars and molars were measured in the virtual casts using CAD/CAM analysis software Results: Results revealed that at a 10-minute time interval, there is no dimensional change seen, whereas at a 20-minute time interval there was a slight change, which is clinically significant, but statistically it is insignificant when immersed for more than 20 minutes. CONCLUSION: There is no significant dimensional change in alginate after 10 minutes of immersion in korsolex, whereas changes in dimensional stability are seen after 20 minutes of immersion with korsolex. This disinfectant is ideal for 10 minutes immersion only.